OPTIMASI FORMULA HAIR TONIC MIKROEMULSI BIOTIN (VITAMIN B7) DENGAN METODE FACTORIAL DESIGN - Fauziyyah Al Hasanah; Gunawan Pamudji Widodo; Endang Dyah Ikasari (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2023)
Loss becomes a problem in the hair that causes baldness. Biotin is a vitamin that nourishes hair and prevents hair loss. Biotin which is formulated in microemulsion tends to be transparent, has low viscosity and high solubility. Formula optimization was carried out to determine the concentration of span 80, tween 80, and PEG 400 in biotin microemulsion hair tonic. The research was conducted on an experimental basis using a factorial design method with 3 factors, namely span 80, tween 80, and PEG 400. The optimum microemulsion formula was determined using Design Expert 13 software using the Factorial Design method. Testing the physical quality of the preparation is carried out at the optimum formula. Optimization of biotin microemulsion hair tonic showed results of span 80 (20%), tween 80 (9.466%) and PEG 400 (5%) with a predicted viscosity of 46.75 cPs and globule size of 2.98 µm. Prediction testing and test results compared to the One Sample T-test showed results that were not significantly different with a significance value of >0.05. The optimum formula has a viscosity value of 47.67 cPs and a globule size of 2.4 µm. The results obtained concluded that the optimal composition composition of the biotin microemulsion formula from the combination of span 80, tween 80 and PEG 400 which produces hair tonic with good effects and physical quality is span 80 20%, tween 80 9.47% and PEG 400 5%.